Synthesis and swelling behavior of bentonite based superabsorbent polymer composities - Ainun Jariah, Sansuri (2010)
A novel superabsorbent polymer composite (SPC) was synthesized by solution polymerization reaction of partially neutralized acrylic acid (AA) and acrylamide (AM) on bentonite micropowder using N,N-methylenediacrylamide (MDA) as croslinker and ammonium peroxodisulfate (APS) as an initiator in aqueous solution. Poly (acrylamide-co-acrylic acid) [poly (AM-co-AA)]-based bentonite SPC were prepared by varying the cross-linking agent composition amount in the range of 0.00% to 1.80%. The effect of Bentonite as filler in weight percentages range of 0.00% to 1.40% on the water absorbency of the hydrogels was also studied by keeping two monomers content constant. The synthesized hydrogels were characterized by FTIR dan SEM. The effect of amount of Bentonite and crosslinker on the water absorbency of AM-AAc-Bentonite was investigated to different physiological fluids which are; deionized water, NaOH solution pH 13.75 and HNO3 solution pH 2.10. An optimum condition which is highest percentages of swelling behavior were obtained with bentonite composition at about 1.00% wt, crosslinker composition in range 1.20-1.40% wt and the best fluid immersed in distilled water. The water absorbency of poly(AA-co-AM)/bentonite was found to be 3821.57, 822.15 and 675.72g H2O g in distilled water, alkali solution and acid solution.